2020
DOI: 10.3389/fsurg.2019.00081
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for the Treatment of Glioblastoma

Abstract: Glioblastoma is the most common form of adult brain cancer and remains one of the deadliest of human cancers. The current standard-of-care involves maximal tumor resection followed by treatment with concurrent radiation therapy and the chemotherapy temozolomide. Recurrence after this therapy is nearly universal within 2 years of diagnosis. Notably, >80% of recurrence is found in the region adjacent to the resection cavity. The need for improved local control in this region, thus remains unmet. The FDA approval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 80 publications
0
106
0
3
Order By: Relevance
“…In addition to sensitizing cytotoxic reactions, ALA-induced PpIX produces a strong red fluorescence under relatively low intensity exciting light. Many oncologists, particularly those treating glioblastoma, have exploited this property for fluorescence-guided resection (FGR), i.e., to clearly demarcate tumor extremities before surgical removal, thereby greatly improving procedural accuracy [9,29,30] . Consequently, ALA-induced PpIX has the advantage of serving as a surgical guide on the one hand and a cytotoxic PDT sensitizer on the other hand.…”
Section: Photodynamic Therapy For Glioblastoma and Other Solid Tumorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to sensitizing cytotoxic reactions, ALA-induced PpIX produces a strong red fluorescence under relatively low intensity exciting light. Many oncologists, particularly those treating glioblastoma, have exploited this property for fluorescence-guided resection (FGR), i.e., to clearly demarcate tumor extremities before surgical removal, thereby greatly improving procedural accuracy [9,29,30] . Consequently, ALA-induced PpIX has the advantage of serving as a surgical guide on the one hand and a cytotoxic PDT sensitizer on the other hand.…”
Section: Photodynamic Therapy For Glioblastoma and Other Solid Tumorsmentioning
confidence: 99%
“…An early study by Gilissen et al [31] using a rat aorta model showed that PDT impairs NO generation by vascular endothelial cells, suggesting that the anti-tumor effects of PDT might be due to vasoconstriction of the tumor reactive oxygen species-based mechanisms are depicted: Type I (free radical) vs . Type II (singlet oxygen) [9] microvasculature. In another in vitro study, Gupta et al [32] reported that nNOS in epidermoid cancer cells was rapidly upregulated by PDT-like stress and that the resulting NO was cytotoxic, enhancing the effects of PDT per se.…”
Section: Role Of No In Pdt Resistance and Cell Aggressiveness: Backgrmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear and present need for significant improvement in treatments for both newly diagnosed and recurrent GBM. Notably, there have been multiple clinical studies investigating photonics-based PDT and fluorescence guided resection (FGR) to better clean the margins and improve survival 16 26 . For these reasons, 5-ALA (a pro-drug) for fluorescence-guided PDT in grade III and IV gliomas has been approved by FDA 18 .…”
Section: Introductionmentioning
confidence: 99%